Dynamic analysis of splenic Th1 and Th2 lymphocyte functions in mice infected with Schistosoma japonicum. - Xu, Y H (1991)
Recent studies indicate that egg granuloma formation in murine Schistosoma mansoni infection is associated with Th2-mediated immune responses. The present study was designed to analyze dynamically the Th1 and Th2 responses in S. japonicum-infected animals and compare them with the results seen with S. mansoni. C3H mice were infected with 10 to 20 cercariae of S. japonicum and sacrificed 3 to 22 weeks later. Spleen cells were stimulated with parasite antigens (egg and adult worm) or the mitogen concanavalin A. Interleukin-2 (IL-2), IL-4, IL-5, and gamma interferon (IFN-gamma) levels were measured in the culture supernatants by enzyme-linked immunosorbent assay (ELISA) or bioassays. Additionally, cytokine-producing cells were enumerated by ELISPOT. The results show that Th2 cytokine production, characterized by IL-4 and IL-5, represents the major response in the first month after egg laying begins, while the Th1 functions of IFN-gamma and IL-2 production are greatly depressed. However, by 22 weeks Th2 responses have diminished and IFN-gamma production in response to concanavalin A is apparent. IL-2 responses are minimal at all times. In vitro depletion of T-cell subsets indicates that CD4+ cells are the major subset responsible for production of IL-5 at 7 weeks of infection. These findings suggest that, as in the case of S. mansoni infection, S. japonicum-induced immunopathology is temporally associated with the host Th2 response, although other experiments indicate that IFN-gamma is also involved.